2007
DOI: 10.1177/145749690709600412
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Comparing Core Data from Existing Trauma Registries in Scandinavia. Reaching for a Scandinavian Major Trauma Outcome Study (MTOS)

Abstract: Background: the organisationo ft raumac arei ns candinavia has several similarities, including trauma registries, but so far there are limited amount of research on efficiency and outcome. data and results from trauma outcome studies like the us mtos are not fully applicable to the scandinavian trauma population.Aims: to reveal the feasibility of usingd ata from existing trauma registries of major hospitals in scandinavia, for aminimal common dataset, in ajoint, prospective scandinavian mtos.Material and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
1
8
0
1
Order By: Relevance
“…Due to differences between trauma registries, the collaboration recognised that meaningful outcome comparisons were not possible. Similar conclusions were also reached in a contemporary Scandinavian report [9]. …”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Due to differences between trauma registries, the collaboration recognised that meaningful outcome comparisons were not possible. Similar conclusions were also reached in a contemporary Scandinavian report [9]. …”
Section: Introductionsupporting
confidence: 91%
“…The introduction of regionalised trauma systems has the potential to reduce preventable deaths [3], but an improved understanding of the benefits and limitations of different trauma care systems requires comparison across systems [4]. However, it has been shown that the datasets of existing trauma registries frequently lack compatible definitions of common data variables [5-9]. Consequently, the comparison and interpretation of trauma system outcomes has been hampered [10].…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty of comparing trauma and critical care between centres and over time based on locally defined data variables has been illustrated in several recent reports [6-8,28]. Over the last two decades, several templates for standardised documentation and reporting in critical care have been published.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of data collected routinely for other purposes may be of variable quality [4,5]. Even in cases in which the data quality is satisfactory, data that are defined and collected for other purposes can create uncontrolled bias and influence external and internal validity [6,7]. Uncontrolled bias and lack of external validity can make the interpretation of results challenging [8] and hinder systematic reviews [9-11].…”
Section: Introductionmentioning
confidence: 99%
“…En Europa, existen diferentes RT surgidos en las Ășltimas dĂ©cadas; muchos son unicĂ©ntricos, aunque algunos, como el alemĂĄn (German National Trauma Registry) 46 48 son multicĂ©ntricos y contienen gran cantidad de pacientes e informaciĂłn. Han surgido iniciativas para llegar a un consenso sobre los datos que debe contener un RT europeo, la forma de recoger esos datos y el manejo estadĂ­stico de los mismos (Utstein Template for Uniform Reporting of Data following Major Trauma) 49,50 , paso previo hacia un registro europeo, que es factible con mĂ­nima infraestructura adicional y usando un sistema basado en la web 51 , aunque de momento no ha avanzado suficientemente.…”
Section: Registros De Trauma En El Mundounclassified